Pattern of fruits and vegetables intake among Health Sciences Students in Public University UiTM Selangor/ Emmy Hainida Khairul Ikram and Shazlen Amera Rohadi - Khairul Ikram, Emmy Hainida; Rohadi, Shazlen Amera (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
World Health Organisation (WHO) recommended public to take at least 400 grams of fruit and non starchy vegetable or five serving combination of them per day. This study examined total number of fruit and vegetable consumed by Faculty of Health Science students UiTM Selangor, Puncak Alam campus and factors associated with their intake. A cross sectional survey of 266 students from Faculty Health Science, aged 19-25 years were chosen and self-reported questionnaire was conducted. The study included 68 (25.6%) male and 198 (74.4%) female participants. The mean for age was 22.06±1.19 and mean BMI was 22.63±4.33. Results indicated that consumption of fruit and vegetable consumption was far less compared with the WHO recommendation. Financial status, residency, availability and accessibility were significantly associated with fruit and vegetable consumption (p <0.001). In contrast, level of BMI and awareness were found to be insignificantly associated with fruit and vegetable consumption. In conclusion, this study illustrated that financial source and residency has a major influence on their fruits and vegetables consumption. Student who are self-financed and live with family have higher intake of fruits and vegetables intake compared other students.